An Exploration on the Expressive Skills among Elementary-grade Learners: A Bedrock for the Development t of Computer-assisted Teaching Strategies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A person’s thoughts, ideas and feelings are expressed through speaking and writing which arecommonly termed as expressive skills. Through these skills, teachers are able to assess the levelof understanding of the learners on a particular lesson that was taught. Employing the descriptive–quantitative-correlational research design, this study aims to assess the level of the speaking andwriting skills of the six grader learners among the selected schools in one of the Division inZamboanga Peninsula. Furthermore, it also sought to know if significant correlation existsbetween the two expressive skills. This study enlisted 180 pupils from different public schoolswhich were chosen through stratified sampling. Using the series of pictures taken from theLanguage Expressway 6 which is a standardized instrument, the respondents where ask to narratea story out of the pictures through speaking and writing. Their oral and written output were thenrated by the three English language teachers using the assessment matrix of DepEd Order no.8,series of 2015.The findings of the study concludes that the speaking and writing skills of the six graderlearners falls below the level of 75% which is the national passing rate of public schools in thePhilippines. Moreover, a positive correlation was noted between the two expressive skills.Hence, the Ha is being accepted. Therefore, it is safe to say that the learners did not meet thelevel of speaking and writing that is expected of them. This result may be associated with theimplementation of the Mother Tongue Based instruction from Grade I-III which focuses on themastery of the L1 of the learners. Perhaps, we may consider that reason for the present level ofspeaking and writing among the six grader learners.